EFFECTS OF COWPEA (VIGNA UNGUICULATA) EXTRACT IN VEGF EXPRESSION OF CORNEAL INFLAMMATION RAT MODEL (RATTUS NOVERGICUS STRAIN WISTAR) - Yuliono Trika Nur Hasan; Nanda Wahyu Anandita; Husnul Khotimah (Saintika Medika, 2014)
Purpose : to evaluate the effects of Methanolic extract of Cowpea (Vigna unguiculata) administration on vascular endothelial growthfactor (VEGF) expression in rats with corneal-alkali induced inflammation.Methods : This was an interventional experimental study. Sixty three rats were randomly selected, 3 rats as control, 60 rats were treatedwith 1 M NaOH (as inflammation model) and administered with 25 ìM,50 ìM and 100 ìM of genistein in Cowpea (Vignaungucuilata) extract four times daily. Alkali burn by 1 M NaOH infiltration using filter paper applicated on the center cornea of righteye for 60 seconds. Aquabidest as positive control and Cowpea (Vigna ungucuilata) extract treatment perfused immediately after alkali burn.VEGF observed at 6, 24, 48, 96 and 168 hours by immunohistochemical method.Results : Each dose of Cowpea (Vigna unguiculata) extract administration significantly decreased the VEGF expression ( p = 0,00). Differences of VEGF expression based on administration time were not significant (p=0,033). Interaction between time of administrationand dose of administration had influenced the VEGF expression (R Square(r2) =24,7 %). The Linear regression between VEGF expression and dose resulted in estimated effective dose (ED) with Y = 16.486–0.079 X( Y = V E G F e x p r e s s i o n , X =d o s e o f a d m i n i s t r a t i o n ) . Considering VEGF expression in normal cornea was 12, wefound the effective dose of methanolic Vigna unguiculata extract was 61.94 ìM.Conclusion :Methanolic extract of Cowpea(Vigna unguiculata) decreased the VEGF expression on alkali burn corneal inflammationin rats but no differences in VEGF expression based on time administration. Dose of 50 ìM genistein in Methanolic extract ofCowpea (Vigna unguiculata) was close to effective dose 61.94 ìM.Keywords : VEGF expression, alkali burn, Cowpea (Vigna unguiculata) extract, cornea.